PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN, DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP INDEKS APOPTOSIS SEL NEURON DI CEREBELLUM RATTUS NORVEGICUS BARU LAHIR - Fajrin, Dessy Hidayati; Joewono, Hermanto Tri; Widjiati, DR (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2085)
The efforts that can be done to improvebrain cells in the prenatal period is the provision ofnutrients and good stimulation. Exposure to classicalmusic such as Mozart, Beethoven, and Chopinmusic can increase the wave of brain activity. Duringpregnancy, Mozart music is proven to decrease theapoptosis of neuronal.Analyzing the difference of apoptosisneuronal of cerebrum and cerebellum of newbornbaby of Rattus norvegicus that are exposed to theMozart, Beethoven, and Chopin music, and that isnot exposed to music during pregnancy.Laboratory experimental research, posttestonly control group design. Subjects were femalepregnant Rattus norvegicus, grouped into 4 randomgroups: 1 control group and 3 treatments groups;with 6 samples each. Subjects were super ovulated,and 65 dB intensity of music is played for an hour at20.00-21.00 on the subjects on 10th day ofpregnancy. On 20th day of pregnancy, the motherswas dissected using SC technique. 2 heaviestnewborn babies of Rattus norvegicus were taken.Statistical test concluded there wassignificant differences of apoptosis neuronal ofcerebellum of newborn babies of Rattus norvegicusamong the exposure to Mozart, Beethoven, andChopin music, and without the exposure to musicwith value of p=0,033 in cerebellum.In conclution, the exposure of Mozart?smusic during pregnancy perform expression ofBDNF cerebellum in the offspring-rat was higherthan exposed Beethoven?s music, Chopin and notexposed to music.